PENGARUH INVESTASI ASING DAN INVESTASI DALAM NEGERI TERHADAP PEREKONOMIAN INDONESIA (Jurnal Kendali Akuntansi, 2023)
Indonesia, with its long-term economic development plan spanning 20 years, divided into five-year medium-term plans, recognizes the importance of both foreign and domestic investments in driving its economic growth. The country presents opportunities across various sectors, as the increasing income levels can influence Indonesian consumers' interest in imported products and services. However, investing in Indonesia comes with unique risks and challenges, considering the country's dynamic context. To ensure successful investments, it is crucial for investors to understand Indonesian culture and the preferences of local consumers. This understanding can help tailor products and services to suit the local market, thus enhancing the chances of success. Additionally, the Indonesian government has implemented strategies to diversify the economy, focusing on priority sectors that can further stimulate economic growth. Foreign and domestic investments play a vital role in contributing to Indonesia's economic growth. These investments not only infuse capital into the country but also bring in technological advancements, job opportunities, and knowledge transfer. To attract investments, the Indonesian government has been implementing policies to improve the ease of doing business and create a favorable investment climate.